2013
DOI: 10.5001/omj.2013.04
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive Protein and Tumor Necrosis Factor Alpha in Pseudoexfoliation Syndrome

Abstract: The results suggest that increased levels of high- sensitivity C-reactive protein and Tumor Necrosis factor alpha, as markers of inflammation and peripheral endothelial dysfunction in pseudoexfoliation syndrome, may be risk factors for systemic and ocular manifestations of pseudoexfoliation syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…12 Sorkhabi et al studied high-sensitivity C-reactive protein and tumor necrosis factor alpha in PEXS and mentioned that increased levels of these markers, as signs of inflammation and peripheral endothelial dysfunction, may be risk factors for systemic and ocular manifestations of PEXS. 13 In contrast, high-sensitivity C-reactive protein had not been found as a predictive marker of inflammation and peripheral endothelial dysfunction in PEXS and PEXG. 14 The inflammation is an important component of other ocular diseases such as age-related macular degeneration (AMD) and vascular diseases of retina.…”
Section: Discussionmentioning
confidence: 99%
“…12 Sorkhabi et al studied high-sensitivity C-reactive protein and tumor necrosis factor alpha in PEXS and mentioned that increased levels of these markers, as signs of inflammation and peripheral endothelial dysfunction, may be risk factors for systemic and ocular manifestations of PEXS. 13 In contrast, high-sensitivity C-reactive protein had not been found as a predictive marker of inflammation and peripheral endothelial dysfunction in PEXS and PEXG. 14 The inflammation is an important component of other ocular diseases such as age-related macular degeneration (AMD) and vascular diseases of retina.…”
Section: Discussionmentioning
confidence: 99%
“…Sorkhabi et al reported that tumour necrosis factor‐α and C‐reactive protein levels in a group with pseudoexfoliation were significantly higher than in controls. In this study, inflammation was also thought to be involved in pseudoexfoliation …”
Section: Discussionmentioning
confidence: 85%
“…In this study, inflammation was also thought to be involved in pseudoexfoliation. 36 Although there have been studies about oxidative damage in lens epithelial cells of patients with pseudoexfoliation, there apparently have been no reports of the level of PEDF in lens epithelial cells in patients with pseudoexfoliation. The present study found that PEDF levels were significantly lower in anterior capsule material of cataract patients with pseudoexfoliation than in those without pseudoexfoliation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Turkyilmaz et al 24 have shown a relationship between PES and elevated serum levels of YKL-40 (chitinase-3-like protein 1), which has a role in endothelial dysfunction and inflammation. To date, elevated serum levels of several other molecules that have definitive roles in inflammatory processes (eg, cardiovascular and cerebrovascular disease, endothelial dysfunction), including high-sensitivity C-reactive protein, 25 tumor necrosis factora, 25 antiphospholipid antibody, 26 a 1-antitrypsin, 27 homocysteine, 28 and hydroxyproline 29 have been studied in the serum of patients with PES. In the present study, serum omentin levels were found to be lower in patients with PES compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%